STRATEGI PEMBELAJARAN PAI BERBASIS AKULTURASI ISLAM NUSANTARA DAN KESADARAN EKOLOGIS - Andi Wahyumulianti; Dika Tripitasari; Ahdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Entering the Anthropocene era, the escalation of global environmental degradation has reached a nadir that threatens the stability of human civilization, necessitating a curriculum reorientation that is more responsive to ecological crises. This study aims to construct an integrative Islamic Religious Education (PAI) learning strategy through a functional synergy between the values of Nusantara Islam Acculturation and the Eco-Theology paradigm. Employing a qualitative design with a Systematic Literature Review (SLR) approach, a profound analysis was conducted on various reputable primary literatures published within the last five years. The research findings reveal that the transformation of ecology-based PAI requires a fundamental reorientation across three interconnected strategic dimensions. First, the conceptual-theological dimension involves repositioning the meaning of 'khalifah' as a nature preserver and strengthening ecological monotheism (tawhid). Second, the institutional-managerial dimension focuses on developing the Eco-Islamic School model, which integrates sustainable waste management systems and strengthens ecological literacy within institutional governance. Third, the practical-methodological dimension implements a transdisciplinary STEM-PAI approach, utilizing digital technology to ground religious values in tangible actions. The synthesis confirms that this strategy not only strengthens national character by preserving Nusantara's local wisdom but also serves as a substantive contribution to the global Sustainable Development Goals (SDGs) agenda, particularly regarding climate action, gender equality, and quality education. This study concludes that the synchronization between religious ethics derived from revelation and global scientific standards is a crucial key to creating a collective social transformation toward a future civilization that is harmonious, inclusive, and sustainable.